Role Of Positron Emission Tomography With Computed Tomography Using F-18 Flurodeoxyglucose In Detection Of Carcinoma Of Unknown Primary In Malaysia - Samsudin, Nursazlinda (2016)
Carcinoma of unknown primary represents a heterogenous group of tumour with well known characteristics and behavior. It is essential to locate the primary tumor to facilitate specific treatment for patients